Ab initio excited-state electronic circular dichroism spectra exploiting the third-order algebraic-diagrammatic construction scheme for the polarization propagator - Scott, Mikael; Rehn, Dirk R.; Norman, Patrick; Dreuw, Andreas (The journal of physical chemistry letters, 2021)
Excited-state rotatory strengths are reported for the first time at a correlated ab initio level, here with the algebraic diagrammatic construction scheme of the polarization propagator up to the third order. To demonstrate the capabilities of this computational approach, the gas phase S1 electronic circular dichroism spectra of the bicyclic ketones (1R)-camphor, (1R)-norcamphor, and (1R)-fenchone have been calculated at the ADC(3) level of theory. Furthermore, the solution excited-state spectra of the energetically lowest conformer of R-(+)-1,1′-bi(2-naphthol) have been computed with inclusion of a polarizable continuum model at the ADC(2) level of theory.
Published online 25 May 2021
Published in issue 3 June 2021
Gesehen am 02.08.2021